Echocardiographic Effects of Adherence to Physical Exercise in Older Adults: Results From the Aga@4Life Cohort - Joaquim Castanheira; Ana Carolina Carvalho; Telmo Pereira (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: Aging is associated with changes in heart structure and function, and there are benefits of physical exercise in delaying these changes. OBJECTIVES: To characterize the heart of a geriatric cohort at a structural and functional level, and to evaluate the potential cardiac benefits of a personalized exercise intervention program. METHODS: Non-randomized intervention study, including a group of old adults from the AGA@4life cohort. Two echocardiographic evaluations were performed, at baseline and 3 months after the implementation of a multidisciplinary intervention program, integrating the practice of adapted physical exercise. Participants were divided into 2 groups: group 1 with low adherence to the exercise program (< 20% of sessions); group 2 with high adherence to the exercise program (> 90% of sessions). RESULTS: Characteristic heart changes were observed at baseline, mainly at the valvular level, with 89.2% (n = 33) cases of aortic fibrosis, 73% (n = 27) cases of mitral fibrosis, 51.2% (n = 19) cases of aortic regurgitation, and 68% (n = 25) cases of mitral regurgitation. After the intervention, significant changes were observed in several functional parameters in group 2, namely in the maximum velocity of the E' (p = 0.01) and S' (p = 0.02) mitral valve waves, and maximum velocity of the E' tricuspid valve wave (p = 0.02). Positive structural changes were also observed in group 2, namely a reduction in relative wall thickness (p = 0.03) and left ventricular diastolic diameter (p = 0.04). CONCLUSION: Personalized physical exercise implemented as part of a multidisciplinary intervention program is a useful non-pharmacological tool for maintaining adequate cardiac function and structure in the old adult.